Intellectual Capital, Company Performance, Sustainable Growth, and Company Value: Analysis of Financial Sector Data in the Indonesia Stock Exchange - Muhammad Arif; Philipus T Paryanto; Priyanto Wisnu Wardhana; Henny Setyo Lestari; Farah Margaretha Leon (Universitas Pendidikan Ganesha, 2023)
The financial sector of IDX is important in the Indonesian economy. This sector consists of various kinds of financial companies, such as banks, insurance companies, and investment companies, all of which have unique characteristics and challenges in terms of the utilization of intellectual capital. Although the financial sector has played a vital role in the Indonesian economy, utilising intellectual capital is still a new phenomenon that has yet to be fully adopted. It needs further study its impact on company performance, sustainable growth, and firm value. Therefore, this research aims to identify the impact of intellectual capital and its components on company performance, sustainable growth, and firm value in the financial sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. The type of research used in this study is quantitative. The research results show that intellectual capital, notably Structural Capital, significantly impacts performance, growth, and firm value in the financial sector on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. Additionally, measuring a company's market value relative to its book value or Tobin's Q significantly affects these three aspects. Therefore, this research can broaden the scope of previous literature that primarily focused on the role of intellectual capital in the manufacturing, technology, and banking sectors by involving data and analysis from the IDX financial sector during the 2019-2022 period.